James Monroe, John Marshall, and "the excellence of our institutions", 1817-1825 - Aschenbrenner, Peter J., author.
1 online resource.
Keywords: "When James Monroe became president in March 1817, the United States urgently needed a national transportation system to connect new states and territories in the west with older states facing the eastern seaboard. In 1824, the Supreme Court declared that Congress had the power to regulate traffic on all navigable rivers and lakes in the United States. Congress began clearing obstructions from rivers, and these projects enabled steamboats to transform cross-country travel in the United States. This book explains how building a nationwide economic market was essential to secure the loyalty of geographically remote regions to the new republic. Aschenbrenner defends the activist role of President James Monroe (1817-1825) and Chief Justice John Marshall (1801-1835), and shows how under their leadership, the federal government made national prosperity its "Job One". The market revolution transformed the daily lives of households and businesses in the United States and proved to Americans that they shared a common social and economic destiny. As Monroe declared at the conclusion of his Presidency: "We find abundant cause to felicitate ourselves in the excellence of our institutions""--